Availability of Phosphorous from Soil and Rock Phosphate as Affected byApplication of Different Organic Matters - Sugiyanto Sugiyanto; John Bako Baon (Indonesian Coffee and Cocoa Research Institute, 2008)
Phosphorus (P) is an important nutrient and often has problem both in its availability in soil and in its supply, therefore direct application of rock phosphate is a prospective alternative. The objective of this research is to study the effect of varied organic matter source on the availability of phosphate derived from soil and rock phosphate. The experiment was laid experimentally in splitplot design and environmentally in randomized complete block design. The main plot was source of P consisted of, control, SP-36 and rock phosphate in dosage of 200 mg P2O5 per kg of air dry soil. Source of organic matter as sub-plot consisted of control (no organic matter), cow dung, cocoa pod husk compost and sugar cane filter cake, each in dosage of 2.5 and 5.0%. Result of this experiment showed that both P and organic matter application affected soil P availability. Application of cow dung and filter cake increased the soil P availability but did not increase the rock phosphate solubility. On the other hand, application of cocoa pod husk did not increase neither soil P availability nor rock phosphate solubility. Filter cake produced higher soil P availability, whereas cocoa pod husk compost produced the lowest which was similar to control (no organic matter). Application of organic matter tended to increase soil pH, exchangeable Ca and available Fe. Changes of available Fe positively correlated with available P. Key words : availability of phosphorus, rock phosphate, organic matter